1989
DOI: 10.1095/biolreprod41.4.753
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin increases Chromatin Solubility in Isolated Bovine and Human Luteal Nuclel1

Abstract: We have previously demonstrated that bovine and human luteal nuclei contain human chorionic gonadotropin/luteinizing hormone (hCG/LH) receptors and that these gonadotropins can directly stimulate nuclear membrane enzyme activity (nucleoside triphosphatase) involved in messenger ribonucleic acid (mRNA) transport from the nucleus to the cytoplasm. The present studies were undertaken to investigate the effect or hCG on chromatin solubility, reflecting perhaps synthesis and transport of RNA, in isolated bovine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Whether this apparent perinuclear immunostaining is due to the natural thickness of the cells in the nuclear region and/or intrinsic receptor distribution is not known. However, previous studies have demonstrated that functional LH/hCG receptors are also present in part in the nucleus of the target cells [27][28][29][30][31]. Preabsorption of the receptor antibody with excess corresponding receptor peptide resulted in an absence of immunostaining (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Whether this apparent perinuclear immunostaining is due to the natural thickness of the cells in the nuclear region and/or intrinsic receptor distribution is not known. However, previous studies have demonstrated that functional LH/hCG receptors are also present in part in the nucleus of the target cells [27][28][29][30][31]. Preabsorption of the receptor antibody with excess corresponding receptor peptide resulted in an absence of immunostaining (Fig.…”
Section: Resultsmentioning
confidence: 98%